2000
DOI: 10.1002/(sici)1097-0088(200005)20:6<587::aid-joc480>3.0.co;2-h
|View full text |Cite
|
Sign up to set email alerts
|

Temporal and spatial variation of surface air temperature over the period of instrumental observations in the Arctic

Abstract: A detailed analysis of the spatial and temporal changes in mean seasonal and annual surface air temperatures over the period of instrumental observations in the Arctic is presented. In addition, the role of atmospheric circulation in controlling the instrumental and decadal‐scale changes of air temperature in the Arctic is investigated. Mean monthly temperature and temperature anomalies data from 37 Arctic, 7 sub‐Arctic and 30 grid‐boxes were used for analysis. The presented analysis shows that the observed va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

11
96
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 112 publications
(110 citation statements)
references
References 75 publications
11
96
0
Order By: Relevance
“…The majority of them focused on air temperature (e.g. Parker et al, 1992Parker et al, , 1994Karl et al, 1995;Plummer, 1996;Przybylak, 1996Przybylak, , 1999Przybylak, , 2000aMichaels et al, 1998;Jones, 1999;Collins et al, 2000;Moberg et al, 2000). Our knowledge during the last decade has grown significantly, but it is still far from complete.…”
Section: Introductionmentioning
confidence: 98%
“…The majority of them focused on air temperature (e.g. Parker et al, 1992Parker et al, , 1994Karl et al, 1995;Plummer, 1996;Przybylak, 1996Przybylak, , 1999Przybylak, , 2000aMichaels et al, 1998;Jones, 1999;Collins et al, 2000;Moberg et al, 2000). Our knowledge during the last decade has grown significantly, but it is still far from complete.…”
Section: Introductionmentioning
confidence: 98%
“…In recent studies, many authors indicated that near−surface air temperature in the Arctic has increased about twice as fast as temperatures in lower latitudes dur− ing the past few decades (Przybylak 2000;Knutson et al 2006;Miller et al 2010). The Svalbard archipelago has been also the subject of many studies that confirmed enormous climate warming, reductions in permafrost thickness, glacier retreat, and changes in vegetation and terrestrial animal habitats (Ziaja 2005;Rachlewicz and Szczuciński 2008;Moreau et al 2009;Prach et al 2012 …”
Section: Introductionmentioning
confidence: 99%
“…As can be seen all stations (except Malye Karmakuly) are located in the coastal parts of Greenland. Przybylak (1996Przybylak ( , 2002 found that temperature changes in this part of the Arctic tend to be independent of each other. As a result, the use of these data to reconstruct the temperature history of the other parts of the Arctic would be inappropriate.…”
Section: Introductionmentioning
confidence: 99%